Maintaining core business and key drivers in mining-Indigenous partnerships: releasing value through recognising difference. - Morgan, H.; Singleton, G.; Rola-Rubzen, Maria Fay (Pearson, 2014)
The chapter presents an Australian case study example of how two mining companies (initialy Newmont Mining Corporation and later, Northern Star Resources Limited) and a Native Title Claim Group (the Wiluna Martu), represented through Central Desert Native Title Service, came together through a mutual partnership based around the acknowledgement of a shared interest in environmental land management, traditional ecological knowledge and meaningful Martu employment. This case study example is bedded within the emerging literature of resource sector corporate social responsibility (CSR) and shared value partnership models. The authors argue that a key aspect of a successful partnership is the understanding that a 'third space' exists between organisations. Value is created through collaboration, flexibility and leveraging resources in ways that enable each organisational culture to maintain its core business and key drivers. Within this paradigm, common value is created and shared, paradoxically, through the recognition that each partner brings fundamentally different resources and capacities to the partnership, which add implicit value to the attainment of respective partners goals.